French criminal justice : a comparative account of the investigation and prosecution of crime in France - Hodgson, Jacqueline (Hart, 2005)
Based on the empirical study of the French pre-trial process, this monograph provides an understanding of the ways in which an inquisitorially rooted criminal process operates in practice, and the factors that influence and constrain its development and functioning. It is useful for those working in the area of criminal justice.